Participation in the Irrigation Sector - Meinzen-Dick, Ruth; Reidinger, Richard; Manzardo, Andrew (World Bank, Washington, DC, 2012)
The irrigation sector provides a rich source of experiences and lessons in user participation. Participation by farmers in system design and management helps to ensure the sustainability of the system, reduce the public expenditure burden, and improve efficiency, equity and standards of service. Mobilizing support at all levels and establishing the participatory process, however, involves costs; it also demands knowledge of the incentives facing each group of stakeholders, and of the essential elements in building effective users organizations.